‘We do it to keep him alive’: bereaved individuals’ experiences of online suicide memorials and continuing bonds - Bell, Jo; Bailey, Louis; Kennedy, David (Mortality, 2015)
This paper presents draws on interviews with individuals who have experience of creating, maintaining and utilising Facebook sites in memory of a loved one who has died by suicide. We argue that Facebook enables the deceased to be an on-going active presence in the lives of the bereaved. We highlight the potential of the Internet (and Facebook in particular) as a new and emerging avenue for the continuation of online identities and continuing bonds. Our study offers unique insight into survivors’ experiences of engaging with the virtual presence of their deceased loved one: how mourners come and go online, how this evolves over time and how the online identity of the deceased evolves even after death. We discuss how Facebook provides new ways for people to experience and negotiate death by suicide and to memorialise the deceased, highlighting the positive impact of this for survivors’ mental health. Finally, we describe the creation of tension amongst those who manage their grief in different ways.
Keywords: Facebook; Suicide; Memorialisation; Internet; Continuing bonds; Grief; Bereavement; Online identity